School Principals’ Practice of Knowledge Management in the Wilayat of Saham in North Batinah Governorate from the Point of View of Teachers - Alshidi, Amal Salim; Al-Nofli, Mohammed Abdullah (Journal of Educational and Psychological Sciences, 2024)
The current study aimed to identify the degree of school principals’ practice of knowledge management in the Wilayat of Saham in North Batinah Governorate from the point of view of teachers. It also aimed to reveal differences in school principals’ practice of knowledge management according to the variables of the study: gender, experience, and qualification. The researcher used the descriptive approach by applying a questionnaire as a tool to collect data for the study. The questionnaire included 40 items distributed into four domains: knowledge generation, knowledge storage, knowledge distribution, and application of knowledge. The study sample consisted of 330 teachers who were selected by the stratified random sampling method from Wilayat Saham schools in the North Batinah Governorate. The results of the study showed that the mean of principals’ practice of knowledge management was 3.67 with a high degree. In addition, the results revealed that there were no statistically significant differences (α ≤0.05) in principles’ practice of knowledge management attributed to the variable of gender, experience, and educational qualification. In light of the results, the study recommended to qualify the administrative staff by conducting training courses and workshops related to new and innovative topics in the technical field and improving school infrastructure.
Keywords: practice; knowledge; knowledge management